Management of supervisory practices during the teaching practicum: perspectives of TESL trainee teachers / Stephanie Anak Larry Daniel - Larry Daniel, Stephanie (2012)
In the field of Teacher Education, the management of supervisory practices is often viewed as a critical role of a supervisor in internship programmes such as the Teaching Practicum. Therefore, the aim of this study was to investigate the management of supervisory practices as perceived by TESL trainee teachers undergoing a three month Teaching Practicum. This study explored aspects such as the trainee teachers' perceptions towards the overall process of supervision, the roles of supervisor, their relationship between supervisees and supervisors and contribution of supervision, The study was conducted at the Faculty of Education in UiTM Shah Alam - a public university located in the state of Selangor in Malaysia. The study involved the total population of Semester Seven and Semester Eight TESL students who had undergone their three month teaching practicum. Therefore a total of fifty eight (58) trainee teachers were involved in this study. The instruments used to collect data included a questionnaire and semi structured interviews. The interviews were conducted with six trainee teachers to triangulate the results obtained from the questionnaire . The findings in this study revealed though positive responses were obtained from the qualitative data, the qualitative data presented rather contradictory findings on a number of aspects. The quantitative findings of the study revealed that a majority of the respondents viewed the supervision process positively as it helped improve their teaching skills and strategies that enhanced their teaching and learning process. They also felt that they had a good relationship with their supervisors. They indicated that their supervisors motivated them and gave them the confidence needed to become effective teachers. On the other hand, qualitative data obtained from interview sessions indicated that some supervisors were not committed in helping students enhance their skills and knowledge during the practicum and a few supervisors were viewed as incompetent, lacking in field experience and demotivating. These findings imply that the management of supervisory practices leave much to be desired and hence the relevant authorities concerned need to look into the role and commitment of supervisors and where possible only competent and experienced supervisors be placed to guide young teacher trainees. This study also recommends that supervisors be provided with continuous training for professional development. Finally, if possible further similar research be conducted involving a larger population sample.